Studi Penafsiran Kisah – Kisah Keluarga Dalam Al-Quran Prespektif Tafsir Al-Misbah Karya M. Quraish Shihab - Nurul Fatimah, Izza; Muhammad Iqbal, Ipmawan; Astuti, Indri (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The recent reluctance of the younger generation to establish a household is a serious problem that must be addressed properly. This phenomenon occurs due to the proliferation of information, especially on social media, about divorce in households due to problems that can actually be anticipated because of the high probability of occurrence in the household. Today's society tends to view marriage as almost having to bring excellent and ideal household conditions, resulting in dissatisfaction and excessive disappointment, which has led to many domestic divorces. The author wants to conduct research to present a new perspective for the community in responding to these problems by examining the interpretation of family stories in the Qur'an. In this research, the author uses the interpretation of M. Quraish Shihab in tafsir al-Misbah as the main reference. This is because tafsir al-Misbah has an adabi ijtima'i style and is written according to the context of Indonesian society by M.Quraish Shihab which we can still find today. This research is a library research (library reseacrh). Library research is research in which all materials come from written materials in the form of books, manuscripts, documents, photographs, and others. The approach used is the maudhu'i interpretation approach. The results showed that the profiles of families mentioned in the Qur'an have a variety of conditions, not all of which meet the requirements of the definition of a sakinah or ideal family proposed by several experts. The author concludes based on the interpretation of the family stories mentioned in the Qur'an, that marriage should not be judged from a material perspective alone, even more important if the success of a marriage is judged by the success of household members in achieving ukhrawi goals with good compromise between its members.